Illocutionary Acts In Courtroom Proceedings: The Contexts Of Local Courts In The Philippines - Catoto, Jerson S. (Community and Social Development Journal, 2023)
Courtroom proceedings gives a lucid picture of the utilization of discourse in the judicial entities. This qualitative study employing content analysis aimed at determining the common illocutionary acts found in the contexts of local courts in the Philippines. Forensic Linguistics is an approach that deals with the relationship between language and law. The Transcripts of Stenographer’s Note (TSN) served as the corpora of the study. Each of the speech acts presented the different views of how language was used during courtroom questioning. Responses of the witnesses articulated their defense in order to provide the vivid picture on every event. Thus, it provided the step-by-step process of knowing the veracity of cases. Through this, the judge can come up with a fair and just decision. The implications provided how Forensic Linguistics played a crucial role in the analysis of texts.